2016
DOI: 10.1103/physrevlett.117.047003
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Precursor of the Pressure-Induced Superconductivity in Fe-Ladder Compounds

Abstract: The pressure effects on the antiferromagentic orders in iron-based ladder compounds CsFe2Se3 and BaFe2S3 have been studied using neutron diffraction. With identical crystal structure and similar magnetic structures, the two compounds exhibit highly contrasting magnetic behaviors under moderate external pressures. In CsFe2Se3 the ladders are brought much closer to each other by pressure, but the stripe-type magnetic order shows no observable change. In contrast, the stripe order in BaFe2S3, undergoes a quantum … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
56
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 38 publications
7
56
4
Order By: Relevance
“…The NPD and µSR results show a gradual increase in T N with pressure followed by an eventual plateau around the highest pressure measured (2.6 GPa), with no observable change in the magnitude of the ordered moment. This contrasts with the abrupt magnetic enhancement around 1 GPa and subsequent reduction reported earlier [22]. Our density functional theory (DFT) calculations reveal a delicate sensitivity of the magnetism on the Fe-S bond lengths and angles, which may explain the discrepancy with the earlier work.…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…The NPD and µSR results show a gradual increase in T N with pressure followed by an eventual plateau around the highest pressure measured (2.6 GPa), with no observable change in the magnitude of the ordered moment. This contrasts with the abrupt magnetic enhancement around 1 GPa and subsequent reduction reported earlier [22]. Our density functional theory (DFT) calculations reveal a delicate sensitivity of the magnetism on the Fe-S bond lengths and angles, which may explain the discrepancy with the earlier work.…”
contrasting
confidence: 99%
“…The NPD results reported so far provide no indication that a change to the ordered moment or ordering temperature occurs between ambient pressure and 1 GPa, in contrast to the dramatic enhancement at 0.95 GPa reported previously [22]. To verify our NPD findings, we now turn to the µSR measurements, which we performed on a sample taken from the same powder batch as was used for the NPD experiments.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…It has been suggested that the abrupt increase of the Néel temperature (T N ) as a function of pressure shown in Fig. 1 (a) is associated with a quantum phase transition due to the change of orbital occupancies under pressure 6 . BaFe 2 S 3 is isostructural with the 1D antiferromagnetic (AF) ladder compounds AFe 2 Se 3 (A = K, Rb, and Cs, space group: Cmcm, no.…”
Section: Pacs Numbersmentioning
confidence: 99%
“…Recently, pressure-induced superconductivity was observed in the two-leg quasi-one-dimensional ladder system BaFe 2 X 3 (X = S, Se) with eletronic density n = 6.0 [9,10], starting a novel field of research for high temperature iron-based superconductors [11][12][13][14][15][16][17][18][19][20][21]. BaFe 2 S 3 displays a stripe-type (CX) AFM order, similar to other 2D iron-based superconductors, below 120 K [9,15]. By applying hydrostatic pressure, this system displayed an insulator-metal transition [16,22] and superconductivity was observed at P ∼ 11 GPa near a first-order magnetic phase transition where the AFM order was suppressed [9,23].…”
Section: Introductionmentioning
confidence: 99%